PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI (Studi Pada PT.Bank Jatim Cabang Tulungagung) - Andreawan Bagus Suminto (Universitas Islam Kadiri, 2020)
The aim of this research analyzing the effect of employee dicipline and compensation to the employee performance in PT Bank Jatim Tulungagung Office. Using multiple linear regression equation by SPSS program version 11.5 to analyze questioner of 73 employee in PT Bank Jatim Tulungagung Office, the result is : Compensation have the biggest effect to the employee performance by 0.591 point regression coefficient. The employee diciplin effected to the employee performance 0.401 point. This result compensation and employee diciplin simultaneous and partial have effected to the employee performance. Compensation have the biggest effect to the employee performance